Cattle grazing and long-term microclimatic fluctuations of simulated rodent burrows - David J. Germano; Lawrence R. Saslaw; Eric Gerber (California Fish and Wildlife Journal)
In the San Joaquin Desert of California, USA, non-native herbaceous vegetation (mostly grasses) has altered the habitat to the detriment of many ground-dwelling species, some of which are protected rodent species. In a natural area, we installed 40 data loggers in simulated burrows that recorded temperature and humidity four times a day for 3.5 years, to determine if the burrow environment was affected by livestock grazing (20 loggers in a grazed plot and 20 in a control plot). We also installed four above-ground loggers (two in grazed and two in control). Although hot (35–40°C) in the summer, burrow temperatures were cooler in the summer and warmer in the winter than above-ground temperatures and had significantly lower daily variability. Humidity values were much higher in burrows throughout the year and significantly less variable daily than above-ground conditions. We found that burrows in the grazed plot were cooler and more humid than burrows in the grass covered control plot, except in winter when conditions were the same. We think that the dense cover of non-native grass in the control plot increased soil moisture loss by acting as a wick that pulled more moisture from the soil when grasses were growing during the spring than in the treatment plot. In areas with high cover of non-native grasses, cattle grazing may benefit burrowing rodents and other vertebrate burrow users by keeping burrows cooler and more humid than if grass cover is not removed.